Personalized Nursing and Health Care - Suhonen, Riitta; Stolt, Minna; Edvardsson, David (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
There has been a rapid development in the academic literature over the last ten years on papers relating to individualization, personalization, patient-, client-, consumer- and person-centredness, with work on conceptual, instrumental, observational, and experimental levels. This Special Issue presents papers that can further establish the current state of science on these topics relating to personalized nursing and health care. We collected papers that highlight and further the knowledge base conceptually, instrumentally, observationally, and experimentally with sound theoretical and methodological underpinnings and implications for research, theory, and clinical work in the disciplines of nursing, medicine, allied health, and beyond.